Strategi Dan Analisis Persaingan Industri Studi Kasus PT Unilever Indonesia Tbk - Aisyah Lulu Fadilah; Ghefira Nur Fatimah; Nabila Yumna Humaimah; Neneng Istikomah; Naerul Edwin Kiky Aprianto (Journal Economic Excellence Ibnu Sina, 2024)
Economic growth that continues to grow rapidly from time to time has a significant impact on the pattern of competition between companies, especially in the manufacturing sector. This competition arises from globalization and the existence of a free market economy caused by the many new companies with similar products as competitors, this triggers competition for market share and the struggle for consumers. Therefore, a strategy is needed in analyzing competition patterns so that companies are able to survive and thrive in the face of competitive market competition. This journal article discusses the strategy and analysis of industrial competition with a case study of PT Unilever Indonesia. In the Uniliver company, there is no doubt that consumer goods are currently very competitive. Several large companies compete fiercely to reach the global market. So PT Unilever must consider a competitive strategy plan. In addition to the main players in the market, Unilever has many other smaller competitors who compete with it in a narrow and specific product space. The discussion in this article explains that there are various strategies for PT Unilever Indonesia in facing competition between companies in the manufacturing sector, including Promotion/Marketing Strategy, Sustainability-Based Strategy, Community Engagement Strategy, Information Technology Strategy, Functional Strategy, and Competitive Profile Matrix (CPM).